Reader, I buried them : [large type] and other stories - Lovesey, Peter (Thorndike Press large print mystery series., 2022)
"More than fifty years ago, Peter Lovesey published a short story in an anthology. That short story caught the eye of the great Ruth Rendell, whose praise ignited Lovesey's lifelong passion for short form crime fiction. On the occasion of his hundredth short story, Peter Lovesey has assembled this devilishly clever collection, eighteen yarns of mystery, melancholy, and mischief, inhabiting such deadly settings as a theater, a monastery, and the book publishing industry. The collection includes that first story that launched his story-writing career as well as three exclusive new stories. In addition, Lovesey fans will delight in a personal essay by the author about the historical inspirations--and in an appearance by the irascible Bath detective Peter Diamond, who has, in the author's words, "bulldozed his way" into this volume"--